2022
DOI: 10.1371/journal.pone.0262046
|View full text |Cite
|
Sign up to set email alerts
|

Evaluation of a novel combination of TRAM-34 and ascorbic acid for the treatment of corneal fibrosis in vivo

Abstract: Corneal injury and aberrant wound healing commonly result in corneal fibrosis and subsequent vision loss. Intermediate-conductance calmodulin/calcium-activated K+ channels (KCa3.1) have been shown to promote fibrosis in non-ocular and ocular tissues via upregulation of transforming growth factor beta (TGFβ). TRAM-34 is a selective inhibitor of KCa3.1 and reduces fibrosis by downregulation of TGFβ-induced transdifferentiation of stromal fibroblasts to myofibroblasts. Ascorbic acid has been demonstrated to be ef… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
4
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(4 citation statements)
references
References 50 publications
(82 reference statements)
0
4
0
Order By: Relevance
“…Our data indicate that at the cellular level, a concentration of 10 µg/mL of vitamin C is sufficient to activate and differentiate primary cardiac fibroblasts, independent of the coating composition and normal or profibrotic settings. It is known TGFβ1 induces the transdifferentiation of fibroblasts to myofibroblasts and contribute to the progression of fibrosis [37]. Our results pointed out the role of vitamin C to also promote primary cardiac fibroblasts' phenotype switching in myofibroblast phenotype and collagen synthesis [38]; however, there are no data to show any correlation between the vitamin C and TGFβ1.…”
Section: Differentiationmentioning
confidence: 59%
“…Our data indicate that at the cellular level, a concentration of 10 µg/mL of vitamin C is sufficient to activate and differentiate primary cardiac fibroblasts, independent of the coating composition and normal or profibrotic settings. It is known TGFβ1 induces the transdifferentiation of fibroblasts to myofibroblasts and contribute to the progression of fibrosis [37]. Our results pointed out the role of vitamin C to also promote primary cardiac fibroblasts' phenotype switching in myofibroblast phenotype and collagen synthesis [38]; however, there are no data to show any correlation between the vitamin C and TGFβ1.…”
Section: Differentiationmentioning
confidence: 59%
“…26 The corneal diseases, including the keratoconus, corneal fibrosis and Fuchs endothelial corneal dystrophy, can also be influenced by the existence of oxidative stress. [27][28][29][30] The corneal endothelium of rabbit eye that underwent benzalkonium chloride insult recovered faster with clear corneal appearance under the application of AA compared to a control group. 19 Moreover, the utilization of AA can lead to the proliferation of human corneal endothelial cells in vitro, 31 and the instillation of AA perioperatively could reduce the damage to the endothelium results from cataract surgery.…”
Section: Discussionmentioning
confidence: 96%
“…Besides, the application of melatonin can ameliorate the oxidative stress‐associated damage in the DED model 26 . The corneal diseases, including the keratoconus, corneal fibrosis and Fuchs endothelial corneal dystrophy, can also be influenced by the existence of oxidative stress 27–30 . The corneal endothelium of rabbit eye that underwent benzalkonium chloride insult recovered faster with clear corneal appearance under the application of AA compared to a control group 19 .…”
Section: Discussionmentioning
confidence: 99%
“…It can effectively clean up the production of reactive oxygen species (ROS) in BMS, promote Nrf2 activity, thereby inhibiting MSC aging and promoting the ability to proliferate and differentiate [30,31]; Secondly, AA also participates as a cofactor in various enzymatic reactions, promoting MSC differentiation into chondrocytes by increasing lysine hydroxylase activity and reducing proline hydroxylase activity [32], while stimulating collagen gene transcription and glycosaminoglycan synthesis, reducing chondrocyte apoptosis [33,34]. Thirdly, the concentration of AA at 0.2 mM can effectively promote the formation of transparent cartilage [28], and studies have also shown that AA can inhibit the expression of TGF-β1 and VEGF and inhibit tissue brosis [15,35,36].…”
Section: Introductionmentioning
confidence: 99%